Electroacupuncture Improves M2 Microglia Polarization and Glia Anti-inflammation of Hippocampus in Alzheimer’s Disease - Xie, Lushuang; Liu, Yi; Zhang, Ning; Li, Chenyu; Sandhu, Aaron F.; Williams, George; Shen, Yan; Li, Hongying; Wu, Qiaofeng; Yu, Shuguang (Frontiers in Neuroscience, 2021)
Background Alzheimer’s disease (AD) is a neurodegenerative disease characterized by loss of recognition and memory. Astrocyte and microglia, as main immune executors in the central nervous system (CNS), take part into the inflammatory activity in AD. Glia polarizes into different phenotypes under neurodegeneration. Pro-inflammatory glia produces cytokines resulting into the debris aggregates and neurotoxicity. Anti-inflammatory phenotypes produce cytokines to release the inflammation. Acupuncture has been found to slow the neurodegeneration. The aim of this study was to uncover the mechanisms of glia activation, microglia polarization and cytokine secretion as a result of acupuncture as a treatment for AD. Methods 20 male SD rats were randomly divided into 4 groups: Control group, Normal saline group, AD group and Acupuncture group. AD and Acupuncture groups were bilaterally injected with Aβ into the CA1 field of the hippocampus. The Acupuncture group received electroacupuncture stimulation on the acupoint ”Baihui”(GV20). The MWM was used to evaluate learning and memory capacity. Immunofluorescence was used to stain GFAP and Iba1 in the hippocampus. The M1 microglia marker and M2 marker were used to stain and analyze the polarization of microglia. The Pro-inflammatory cytokines ,anti-inflammatory cytokines and pathway-molecules were tested to analyze the glia inflammatory response by immunofluorescence and PCR. Results The MWM results showed that acupuncture improves the escape latency time and the swimming distance . The number of GFAP and Iba1 cells significantly increased in AD rats but acupuncture decreased. The iNOS positive cells was significantly increased in AD and acupuncture decreased the positive cells. Acupuncture elevated Arg1 positive cells in AD rats. Acupuncture decreased the glia pro-inflammatory cytokine expression and increased the anti-inflammatory cytokine expression in AD rats. Furthermore, acupuncture inhibited the NF-κB pathway molecule(p65) while raising the Stat6 pathway molecule (Stat6). Conclusions These results provide evidence that acupuncture improves the recognition abilities and memory of AD rats. Acupuncture inhibits the activation of glia and polarizes microglia towards the M2 phenotype. Acupuncture decreased the pro-inflammatory cytokines (IL-1β, TNF-α and IL-6) and increased the anti-inflammatory cytokines (IL-4 and IL-10). Furthermore, acupuncture effects the immune responses through inhibition of NF-κB pathway but activation of Stat6 pathway.